Evaluating climate change impacts on habitat suitability for Iberian freshwater crab “Potamon ibericum Bieberstein, 1808” in Iran - Ghasemian Sorboni, Saman; Hadipour, Mehrdad; Chen, Jit Ern; Pourebrahim, Sharareh (Frontiers in Ecology and Evolution, 2025)
Potamon ibericum, a freshwater crab species, is highly sensitive to environmental changes, especially water temperature and flow regimes. This sensitivity makes it an excellent bioindicator for assessing the health and stability of freshwater ecosystems under climate change scenarios. However, its limited dispersal ability makes it vulnerable to habitat fragmentation and climate-induced range shifts. Therefore, predicting its future habitat suitability is crucial for early conservation planning. This study utilizes current and future (2060–2080) climate variables along with species distribution modeling (SMD) tools. By collecting presence records of the species from various datasets and published articles, we examined its potential distribution. The results indicated that temperature seasonality is the most significant factor influencing the species’ distribution. Additionally, with increasing climatic changes, the species’ altitude range shifts to higher elevations, averaging between 1,600 and 1,900 meters above sea level. We also assessed the degree of overlap between Iran’s protected areas and the current and future suitable habitats for the species. The findings revealed that the most important refuge is the Central Alborz Protected Area, which encompasses approximately 1,803 square kilometers of suitable habitat. However, future projections under the most severe climate scenarios suggest that less than one-fifth of the suitable habitat will remain within protected areas. In general, P. ibericum may face the risk of extinction and significant loss of suitable habitat in Iran due to extreme future climatic conditions. Protecting this sensitive and ecologically important species within freshwater ecosystems is vital, and immediate management actions are necessary to ensure its conservation.